2010
DOI: 10.1158/0008-5472.can-10-0052
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Insulin-like Growth Factor Receptor Translocates to the Nucleus of Human Tumor Cells

Abstract: The type 1 insulin-like growth factor receptor (IGF-1R) is a transmembrane glycoprotein composed of two extracellular α subunits and two β subunits with tyrosine kinase activity. The IGF-1R is frequently upregulated in cancers and signals from the cell surface to promote proliferation and cell survival. Recent attention has focused on the IGF-1R as a target for cancer treatment. Here, we report that the nuclei of human tumor cells contain IGF-1R, detectable using multiple antibodies to α-and β-subunit domains.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
214
4
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(245 citation statements)
references
References 22 publications
22
214
4
5
Order By: Relevance
“…An initial report of intact IGF-1 receptors present in the nucleus (Chen and Roy 1996) has been confirmed and extended in recent reports from two groups (Aleksic et al 2010;Deng et al 2010;Sehat et al 2010). Both groups indicate that this relocalization from plasma membrane to nucleus is IGF-1 dependent and that the nuclear receptor may function as a transcriptional coactivator.…”
Section: Igf-1mentioning
confidence: 65%
“…An initial report of intact IGF-1 receptors present in the nucleus (Chen and Roy 1996) has been confirmed and extended in recent reports from two groups (Aleksic et al 2010;Deng et al 2010;Sehat et al 2010). Both groups indicate that this relocalization from plasma membrane to nucleus is IGF-1 dependent and that the nuclear receptor may function as a transcriptional coactivator.…”
Section: Igf-1mentioning
confidence: 65%
“…47,48 It seems possible that differential receptor downstream signals and nuclear translocation of the IGF1R have a higher impact on IGF1R signaling in cancer cells than receptor expression levels alone.…”
Section: Massoner Et Almentioning
confidence: 99%
“…Overexpression of IGF1R is frequently observed in tumor cell lines and human cancers including non-small cell lung cancer (NSCLC) and mediates both tumor growth and resistance to EGF receptor (EGFR/ ERBB) inhibitors (6). Compelling new data have shown that both the a and b subunits of IGF1R can translocate to the nucleus and directly regulate transcription (7). Nuclear IGF1R has been detected in tumor cell lines and tumor biopsies, and early data suggest an association with poor prognosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Compelling new data have shown that both the a and b subunits of IGF1R can translocate to the nucleus and directly regulate transcription (7). Nuclear IGF1R has been detected in tumor cell lines and tumor biopsies, and early data suggest an association with poor prognosis (7). IGF1R has also been implicated in the ability of drug-resistant cancer cells to maintain viability (8).…”
Section: Introductionmentioning
confidence: 99%